Penerapan Teknik Sosiodrama Melalui Bimbingan Kelompok untuk Meningkatkan Percaya Diri Remaja - Setyawati, Erna; Amirullah, M; Anugerah, Muhammad Fahmi (Indonesian Journal of School Counseling: Theory, Application, and Development, 2022)
Confidence is a very important factor in influencing one's success, self-confidence. Many of a person's success is determined by self-confidence. because with confidence one becomes optimistic, and firm in making decisions. With a strong belief that a person gains great strength in achieving success. Confidence is obtained through many processes, not innate or inherited from birth. Self-confidence does not just come but is influenced by various factors in life. Therefore, self-confidence is the result of an interactive process, so self-confidence can be developed. One way to develop or increase self-confidence is by using sociodrama techniques. Sociodrama is a technique in group guidance, namely role play aimed at solving social problems that arise in human relations. With the sociodrama technique, it is hoped that the self-confidence of these teenagers can increase. Because adolescent self-confidence is influenced by their social interactions, for this reason, sociodrama is an appropriate technique for increasing self-confidence